Partisipasi Forum Anak Banyumas dalam Mewujudkan Kabupaten Layak Anak di Kabupaten Banyumas Ditinjau dari Perspektif Multi Stakeholder Partnerships - Irma Alviana; Slamet Rosyadi; Simin Simin; Rukna Idanati (Universitas Serang Raya, 2021)
The Children's Forum is a forum for children's participation in development that bridges children's aspirations to the government. Child-friendly Cities/Districts aim to ensure the fulfillment of children's rights in a city/district. Both were formed by the Ministry of Women's Empowerment and Child Protection, so their existence is interrelated with each other. In Banyumas Regency both have been formed, so that with the presence of the Banyumas Children's Forum, participation can be analyzed as an effort to create a Child-friendly City in Banyumas Regency. This study aims to find out how the participation of the Banyumas Children's Forum in realizing Child-friendly City in Banyumas Regency is viewed from the perspective of multi-stakeholder partnerships using descriptive qualitative research methods. The selection of informants used was purposive sampling technique. Collecting data using interview, documentation and observation methods and data analysis methods using interactive analysis methods. The results showed that the Banyumas Children's Forum was formed by a Decree of the Banyumas Regent, fostered by the Banyumas Regent, and facilitated by the facilitators. However, the relationship between the facilitator and the Banyumas Children's Forum has not been closely intertwined because the task of the facilitator is conditional if the Children's Forum needs assistance. For the Child-friendly City program, it is the responsibility of all stakeholders, including the Banyumas Children's Forum which is included in the Banyumas Child-friendly City Task Force. The Banyumas Children's Forum is included in one of the institutional cluster indicators, which are responsible for realizing Child-friendly City. Therefore, to help realize a Child-friendly City, a Children's Forum has now been formed in 27 sub-districts throughout Banyumas, and it is being targeted to establish a Children's Forum in all villages. The activities of the Banyumas Children's Forum are monitored and evaluated directly by the Banyumas Regent as the supervisor and the Head of the Section for the Fulfillment of Children's Rights of the DPPKBP3A.